2016
DOI: 10.1371/journal.pone.0158128
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Thermal and Non-Thermal Processing of Swine Feed and the Use of Selected Feed Additives on Inactivation of Porcine Epidemic Diarrhea Virus (PEDV)

Abstract: Infection with porcine epidemic diarrhea virus (PEDV) causes diarrhea, vomiting, and high mortality in suckling pigs. Contaminated feed has been suggested as a vehicle of transmission for PEDV. The objective of this study was to compare thermal and electron beam processing, and the inclusion of feed additives on the inactivation of PEDV in feed. Feed samples were spiked with PEDV and then heated to 120–145°C for up to 30 min or irradiated at 0–50 kGy. Another set of feed samples spiked with PEDV and mixed with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 32 publications
(38 reference statements)
1
50
0
2
Order By: Relevance
“…Addition of salt, but not sugar, to the control diet caused a decrease in delta values for inactivation of PDCoV. This observation is in agreement with inactivation of PEDV in complete swine feed, where adding both salt and sugar increased inactivation of PEDV [20]. Likewise, this observation is in agreement with results from an experiment that suggest that addition of phosphate supplemented salt mix to casting for sausage manufacturing increases inactivation of several viruses affecting swine such as Food and Mouth Disease Virus, Classical Swine Fever Virus, Swine Vesicular Disease Virus, and African Swine Fever Virus [23].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Addition of salt, but not sugar, to the control diet caused a decrease in delta values for inactivation of PDCoV. This observation is in agreement with inactivation of PEDV in complete swine feed, where adding both salt and sugar increased inactivation of PEDV [20]. Likewise, this observation is in agreement with results from an experiment that suggest that addition of phosphate supplemented salt mix to casting for sausage manufacturing increases inactivation of several viruses affecting swine such as Food and Mouth Disease Virus, Classical Swine Fever Virus, Swine Vesicular Disease Virus, and African Swine Fever Virus [23].…”
Section: Discussionsupporting
confidence: 83%
“…Comparing data from this experiment with data on inactivation of PEDV, it appears that PDCoV is more labile than PEDV to environmental temperature and storage conditions because the delta values for PDCoV were, in general, much less (<2 d) than 17 days observed for PEDV [20]. Comparison of inactivation kinetics suggest that PEDV resists inactivation during feed storage to a greater extent than does PDCoV.…”
Section: Discussionmentioning
confidence: 70%
“…More extreme temperatures have also been evaluated in which 145°C inactivated PEDV after 10 min (Trudeau et al, 2016). When comparing the previous studies to the present study, the use of a pellet mill inactivated PEDV at a faster rate (30 s) and much lower temperature (54.4°C).…”
Section: Discussionmentioning
confidence: 72%
“…Aside from biosecurity plans and preventative measures, other physical methods of mitigating biological hazards include irradiation and thermal processing. Irradiation using gamma, ultraviolet (UV), or electron beam radiation has been demonstrated to reduce PEDV load by 3-log (Trudeau et al, 2016). Wilson et al (2015Wilson et al ( , 2016 demonstrated the feasibility of using infrared radiation to decontaminate raw pet food ingredients; depending on initial moisture content of the ingredients, infrared heating intensity, and tempering duration, up to 3-log of mycotoxigenic fungi was reduced.…”
Section: Physical Methodsmentioning
confidence: 99%